Physical, chemical, and water absorption characterisitics of tropical maize hybrids - Maziya-Dixon, B.B.; Kling, J.; Okoruwa, A. (2000)
Hybrids adapted to West and Central Africa were developed by the International Institute of Tropical Agriculture (IITA) in the 1980s, which enable the establishment of several private seed companies in Nigeria. Despite the superior agronomic performance of hybrids, farmers still prefer their traditional cultivars in some areas because they posses desired storage and processing characteristics for local maize dishes. A study was conducted to evaluate physical, chemical and water absorption characteristic of eleven tropical maize hybrids developed at IITA as indicators of their suitability for common end- uses in the region. Significant different were observed among hybrids for all the parameters investigated but none of the hybrids excelled in all quality characteristics. Hybrid 8644-31 had relatively high test weight, thousand kernel weight, hardness index, percent protein, ash, and crude fibre. However, it was low in sugar content total sugar, and water absorption index in grain. Protein, ash, crude fibre, starch, amylase, and amylopectin values for all hybrids fell within normal range for maize. Value for all total sugar ranged from 3.04 to 5.69% and fat content range from 3.35 to 9.80%. Nearly all the hybrids had fat content values which were higher than those reported elsewhere for normal maize. The presence of genetic variation among the hybrids suggests that potentials exist for improvement of grain quality to suit specific processing and food use requirements through selection and breeding. Breeding programmes in developing countries should target hybrid development to meet the requirement of producers, processors, and consumers.